Chemical constituents of Chirita drakei Burtt collected in Ha Long bay, Quang Ninh province, Viet Nam. Part 1. Compounds isolated from the n-hexane and ethyl acetate extracts. - Hoang Anh, Nguyen Thi; Tuan, Nguyen Van; Quan, Tran Duc; Thien, Dao Duc; Tam, Nguyen Thanh; Kim Lien, Giang Thi; Thuy, Trinh Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2017)
Two triterpenes, an anthraquinone, two lignans and a phenolic compound were isolated from the n-hexane and ethyl acetate extracts of the aerial part of Chirita drakei Burtt collected in islands, on mountain slopes of Ha Long bay, Quang Ninh province. Their structures have been elucidated by mass, NMR spectroscopy and comparison with published data. There are no report on the chemical constituents of Chirita drakei before our study. Keywords. Chirita drakei, triterpene, anthraquinone, lignin.